2016
DOI: 10.1038/srep26074
|View full text |Cite
|
Sign up to set email alerts
|

Essential amino acids: master regulators of nutrition and environmental footprint?

Abstract: The environmental footprint of animal food production is considered several-fold greater than that of crops cultivation. Therefore, the choice between animal and vegetarian diets may have a relevant environmental impact. In such comparisons however, an often neglected issue is the nutritional value of foods. Previous estimates of nutrients’ environmental footprint had predominantly been based on either food raw weight or caloric content, not in respect to human requirements. Essential amino acids (EAAs) are ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 45 publications
4
69
1
4
Order By: Relevance
“…In general, the concentrations of the amino acids in the genotypes did not differ significantly, except for glutamic acid and histidine (Table 1). High contents of aspartic acid and leucine were also observed in all the snap bean genotypes, agreeing with the data of Sgarbieri et al (1979) and of Tessari et al (2016), who found values that ranged from 13.8 to 14.5 g / 100 g for aspartic acid and from 8.85 to 9.94 g / 100 g for leucine, similar concentrations to those found in the present study. The UEL 415 genotype showed a higher glutamic acid concentration (12.9 g / 100 g) than the UEL 405 (10.9 g / 100 g) and UEL 1 (10.8 g / 100 g) genotypes, while the UEL 2 genotype had a higher concentration of histidine as compared to UEL 405 (2.13 and 1.67 g / 100 g, respectively).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In general, the concentrations of the amino acids in the genotypes did not differ significantly, except for glutamic acid and histidine (Table 1). High contents of aspartic acid and leucine were also observed in all the snap bean genotypes, agreeing with the data of Sgarbieri et al (1979) and of Tessari et al (2016), who found values that ranged from 13.8 to 14.5 g / 100 g for aspartic acid and from 8.85 to 9.94 g / 100 g for leucine, similar concentrations to those found in the present study. The UEL 415 genotype showed a higher glutamic acid concentration (12.9 g / 100 g) than the UEL 405 (10.9 g / 100 g) and UEL 1 (10.8 g / 100 g) genotypes, while the UEL 2 genotype had a higher concentration of histidine as compared to UEL 405 (2.13 and 1.67 g / 100 g, respectively).…”
Section: Resultssupporting
confidence: 93%
“…Legumes, such as beans, soybeans, peas, lentils, peanuts and other pod plants have played an important role in the traditional diets of many countries, besides constituting an excellent source of protein (Sgarbieri et al, 1979;Messina, 1999). The nutritive value of snap bean proteins depends mainly on their free amino acid content, of which leucine and glutamic acid should be highlighted due to the high levels found in beans and other legumes (Sgarbieri et al, 1979;Gonzalez-Castro et al, 1997;Tessari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While calories are widely used to quantify food system performance, protein-which is often invoked as the key nutritional asset of meat-offers an important complementary dimension (Tessari et al 2016). The flow of protein in the American livestock production system, which supplies ≈45 g protein person −1 d −1 to the MAD, is shown in figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Substitution of other food items with other nutritionally similar animal food items is also plausible (e.g., pork for beef), yet the food gains expected from such replacements are considerably lower (see supplementary data). Substitution of beef with non-meat animal based products (dairy and eggs) is possible on a caloric or protein basis (see supplementary data), yet given their dissimilar nutritional profile, a more elaborate methodology is required to construct and analyze such a shift (Tessari et al 2016). The dietary shift potential of replacing beef with a plant based alternative (dominated by legumes) (Eshel et al 2016) amounts to ≈190 million additional people.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean serves as an oil seed crop, feed for animals, protein source for human, and biofuel feedstock 4 . Production of high protein requires less land and exhibits a smaller carbon footprint than producing the same protein from animal or plant sources 5 . Maintaining soybean economic advantage will require study of the seed quality factors and their degree of linkage with genetics, environment, and management (G × E × M).…”
Section: Introductionmentioning
confidence: 99%